#### Answer

$9\sqrt[3] {z}$

#### Work Step by Step

$ 8\sqrt[3] {z}+\sqrt[3] {z}= (8+1)\sqrt[3] {z} = 9\sqrt[3] {z}$
Combine like radicals.

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$9\sqrt[3] {z}$

$ 8\sqrt[3] {z}+\sqrt[3] {z}= (8+1)\sqrt[3] {z} = 9\sqrt[3] {z}$
Combine like radicals.

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.